2021
DOI: 10.3389/fnut.2021.798038
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Phytonutrients Flavonoids Influencing Gut Microbiota in the Prophylaxis and Treatment of Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD), characterized by the chronic inflammation of the gastrointestinal tract, is comprised of two idiopathic chronic intestinal inflammatory diseases. As the incidence of IBD increases, so does the need for safe and effective treatments. Trillions of microorganisms are colonized in the mammalian intestine, coevolve with the host in a symbiotic relationship. Gut microbiota has been reported to be involved in the pathophysiology of IBD. In this regard, phytonutrients flavonoids have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 226 publications
(228 reference statements)
0
35
0
Order By: Relevance
“…Numerous studies have shown that probiotics improve the clinical outcome of IBD patients by in uencing host gut microbiota [32]. Herein, we performed a shotgun metagenomic analysis to investigate whether Lp082 can improve gut dysbiosis in the UC mice model.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that probiotics improve the clinical outcome of IBD patients by in uencing host gut microbiota [32]. Herein, we performed a shotgun metagenomic analysis to investigate whether Lp082 can improve gut dysbiosis in the UC mice model.…”
Section: Discussionmentioning
confidence: 99%
“…without inhibition of commensal bacteria (clostridia and lactobacilli) has been linked to prebiotic polyphenol intake ( Lee et al, 2006 ; Tuohy et al, 2012 ; Duda-Chodak et al, 2015 ). Separate in vivo feeding trials with berry species (cranberry and grape) led to consistent decrease in proportion of Firmicutes to Bacteroidetes, and remarkable increase in growth of Akkermansia muciniphila in the microbial community ( Anhe et al, 2014 ; Roopchand et al, 2015 ; Wang et al, 2021 ).…”
Section: Gut Microbiome and Cognitionmentioning
confidence: 93%
“…and Bifidobacteria spp. and inhibiting gut pathogens ( Wang et al, 2021 ). Reduced abundance of pathogenic bacteria in the gut ( Clostridium perfringens , C. difficile , and gram-negative Bacteroides spp.)…”
Section: Gut Microbiome and Cognitionmentioning
confidence: 99%
“…[77][78][79][80][81] Dietary polyphenols such as flavonoids play an important role in maintaining intestinal homeostasis and possess the ability to modulate the gut microbiome in a variety of ways, such as influencing the abundance of various pathogenic bacteria, and may play a role in the amelioration of IBD-associated dysbiosis. 82,83 In this light, future studies focusing on novel flavonoids such as 2-D08, transilitin and myricetin and their effects on intestinal pathologies linked to dysbiosis are warranted. Interestingly, topoisomerase 1, the primary target of irinotecan, has been identified as a substrate for SUMOylation, with SUMOylation playing an important role in the nucleolar delocalisation of this protein.…”
Section: Papermentioning
confidence: 99%